Implementasi Media Digital Myon terhadap Kemampuan Literasi, Minat Baca dan Hasil Belajar Bahasa Inggris Kelas IV SD XYZ Jakarta - Henny Rouly Elizabeth Sitorus (Syntax Corporation Indonesia, 2024)
Literacy skills are crucial for students in the 21st century, as a student's ability to self-process learning greatly depends on these literacy skills. However, some studies indicate a decline in literacy activities among them. With the rapid development of the digital media and the high use of gadgets among schoolchildren, it is expected that these gadgets can enhance their literacy skills, reading interests, and English learning outcomes. This research aims to determine the effect of using the myON digital media on the students' literacy skills, reading interests, and English learning outcomes. A pre-experimental design was employed to observe the differences before and after the use of the myON digital media, followed by a mixed-method design with an explanatory sequential approach. The research population consisted of 48 Grade IV students. The research instruments included literacy skills worksheets to observe the differences between the pretest and posttest, an N-Gain test was conducted, with the analysis showing an increase classified as low (g ≤ 0.3). A questionnaire was used to assess the impacts of the myON media on their reading interests and English learning outcomes. A simple linear regression analysis was applied, and the results have indicated a significant value > 0.05 for both variables, stating that there has been no significant influence from using myON on the students' reading interests and English learning outcomes.